(untitled) (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2005)
Abstract This paper outlines how Humboldt’s life and work have been influenced by his general interests in Russia, his researches related to that country, and his relationships with individual Russians. Humboldt’s manifold Russian researches cannot be limited to his great expedition of 1829, but extend much more widely. This paper summarizes the topical state of knowledge in this field, and indicates the need for further researches into Humboldt’s relationship with Russia. Zusammenfassung Es wird überblicksweise dargelegt, wie sich Alexander von Humboldts Rußlandinteressen, seine einschlägigen Forschungen und seine Rußlandbeziehungen in Biographie und Werk niedergeschlagen haben. Dabei wird davon ausgegangen, daß sich Humboldts Rußlandbeziehungen nicht in seiner Rußlandreise von 1829 erschöpfen, sondern über diese Reise wesentlich hinausgehen. Die gewählte thesenhafte Darstellung soll den heute in diesen Fragen erreichten Kenntnisstand knapp und übersichtlich resümieren, zugleich aber auch verdeutlichen, daß sich der Forschung noch weitere Aufgaben stellen.